2002
DOI: 10.1366/000370202321115779
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Powder Properties on the Intensity of Raman Scattering by Crystalline Solids

Abstract: The effect of particle size on Raman intensity has been measured for a number of crystalline solids with a fiber-optic-based Raman spectrometer. Particle sizes ranged from 76 to 605 μm. Materials examined were sodium nitrate, sodium chlorate, sodium bromate, potassium ferrocyanide, potassium ferricyanide, and copper(II) sulfate. Raman intensity was found to decrease with increasing particle size. The factors responsible for this trend are discussed. We conclude that the major factor is diffuse reflectance that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
46
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 11 publications
12
46
1
1
Order By: Relevance
“…Although grinding can reduce the variation in particle size, in our case this was avoided because of the requirement to analyse directly the powdered samples with minimal pretreatment. Results showed the band intensity of R-omeprazole to be decreased due to increased particle size [24]. Samples were further studied using TA (drug disks) and by DSC (powder form) in order to further differentiate between amorphous and crystalline forms.…”
Section: Resultsmentioning
confidence: 99%
“…Although grinding can reduce the variation in particle size, in our case this was avoided because of the requirement to analyse directly the powdered samples with minimal pretreatment. Results showed the band intensity of R-omeprazole to be decreased due to increased particle size [24]. Samples were further studied using TA (drug disks) and by DSC (powder form) in order to further differentiate between amorphous and crystalline forms.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, as particle size has been reported to influence peak intensity and/or width [35,48,49], form III of different size ranges was measured by Raman spectroscopy. The spectral variances became negligible after processing (MSC and first derivative calculation) for PLS analysis.…”
Section: Quantitation Of the Binary Mixturesmentioning
confidence: 99%
“…Therefore, overall Raman scattering decreases because the sample volume irradiated decreases (D'orazio & Schrader 1976;Schrader et al 1991). However, in contrast to this theory and early work, more recent studies observed increased peak intensities of powdered inorganic salts as particle size decreased (Pellow-Jarman et al 1996; Wang et al 2002). This discrepancy is probably due to sampling geometry effects.…”
Section: Y Xbmentioning
confidence: 88%
“…The Kubelka-Munk model assumes confocal excitation and collection, although this is not the case in many Raman setups, including those with probes. In these situations, increased diffuse reflectance improves the overlap between the excitation and collection beams, overriding the decrease in sampling volume, thus leading to an overall increase in the detected Raman response (Wang et al 2002). Wang et al (2002) also found that sample thickness, the surrounding medium (e.g., air or water) and sample compression also affected the spectra through diffuse reflectance and sampling geometry.…”
Section: Y Xbmentioning
confidence: 93%